A CORBA-Based Object Framework with Patient Identification Translation and Dynamic Linking - Wang, C.; Ohe, K. (Methods of Information in Medicine, 1999)
Exchanging and integration of patient data across heterogeneous databases and institutional boundaries offers many problems. We focused on two issues: (1) how to identify identical patients between different systems and institutions while lacking universal patient identifiers; and (2) how to link patient data across heterogeneous databases and institutional boundaries. To solve these problems, we created a patient identification (ID) translation model and a dynamic linking method in the Common Object Request Broker Architecture (CORBA) environment. The algorithm for the patient ID translation is based on patient attribute matching plus computer-based human checking; the method for dynamic linking is temporal mapping. By implementing these methods into computer systems with help of the distributed object computing technology, we built a prototype of a CORBA-based object framework in which the patient ID translation and dynamic linking methods were embedded. Our experiments with a Web-based user interface using the object framework and dynamic linking through the object framework were successful. These methods are important for exchanging and integrating patient data across heterogeneous databases and institutional boundaries.
Keywords: CORBA; Object Framework; Patient ID Translation; Dynamic Link; Exchange of Patient Data